Empowerment of Coastal Communities: Hygienic Management of Seaweed - Imamu Akinjide (Journal of Universal Community Empowerment Provision, 2023)
Many coastal communities around the world rely on seaweed for economic, cultural, and environmental reasons. However, poor hygienic practices can compromise the quality and safety of seaweed products, which can have consequences for public health and the environment. Establishing quality control systems, employing clean and safe saltwater, and adopting excellent manufacturing methods are just a few of the initiatives highlighted in this research that can be undertaken to empower coastal communities. Economic potential, environmental safeguards, public health, and cultural preservation are only some of the many advantages of seaweed hygienic management. Finally, it is suggested that stakeholders and policymakers maintain their support for and promotion of seaweed hygienic management to empower coastal communities and guarantee long-term economic growth, environmental protection, public health, and cultural preservation.